Pengaruh Flash Sale dan Affiliate Marketing Tiktok Shop terhadap Pembelian Impulsif Pada Mahasiswa Universitas Sains dan Teknologi Komputer (STEKOM) Siliwangi - Shabrina Rahmawati; Dewi Widyaningsih; Myra Andrianan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of flash sales and affiliate marketing on the TikTok Shop platform on impulse buying behavior among students at the University of Computer Science and Technology (STEKOM) Siliwangi. The increasingly prevalent phenomenon of bold shopping through social media, particularly TikTok, has prompted the emergence of new marketing strategies such as flash sales, which offer short-term discounts, and affiliate marketing, which involves individual promoters to attract consumer interest. This study used a quantitative approach with primary data collected through questionnaires. The study population was all STEKOM Siliwangi students, with a sample size of 100 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression with the help of SPSS. The results showed that flash sales had a positive and significant effect on impulse buying. Similarly, TikTok Shop affiliate marketing also had a positive effect on impulse buying. Simultaneously, both variables contributed significantly to driving students' impulsive buying behavior. These findings suggest that interactive and time-based digital marketing strategies can increase consumers' propensity to make impulsive purchases.